Using a functional C84 monolayer to improve the mechanical properties and alter substrate deformation. Issue 59 (28th June 2015) - Lee, Wen-Jay; Ho, Mon-Shu; Huang, Chih-Pong; Chou, Che-Fu; Tsai, Jyun-Hwei; Su, Wan-Sheng
<x xml:space="preserve">Abstract</x> Contact stress–distance curves and snapshots of deformation of the C84/Si specimen in the indentation process.